Temporal and spatial variation in seismicity connected with few earthquakes in Himalayas as precursor to earthquakes - DUBE , R.K.; CHATTERJEE, S.N. (MAUSAM, 1979)
. Experiments made on rock samples in laboratory and rock bursts in mines (Brady 1975, 1976) have shown that four phases. viz., dilatant; inclusion, crack closure and finally failure. precede fault growth. These behavioural phases have been found to be scale invariant and thus find application to earthquake processes. Spatial and temporal variations of seismicity in the aftershock area of seven earthquakes, within magnitude (Mb) range of 5 to 6.2, which took place in Himalayas, have been observed and the above concept has been used for earthquake prediction. Empirical relations have been obtained to predict the magnitude and time of occurrence of an impending earthquake.